Performance of laying pullets fed microbial combinations up to eighteen weeks of age/ the age of sexual maturity - SHARMA, K S; SHARMA, V K; KUMARI, M; KATOCH, SHIVANI; KAISTHA, MUKUL; KATOCH, B S (The Indian Journal of Animal Sciences, 2014)
Comparative dietary response of the combinations of different strains of lactobacilli, streptococci and yeast isolated from indigenous sources was studied in commercial egg type chicken, Various treatments consisted of T1 (control culture medium), T2 (Lactobacillus bulgaricus L4 + Streptococcus lactis SI +Saccharomyces cerevisiae Y3), T3 (L. plantarum carrot + S. jaecium onion + S. cerevisiae crow), T4 (L. salivarlus cauliflower + S.faecium banana + S. cerevisiae food yeast), T5 (L. acidophillus leopard + S feacalis leopard + Tornlopsis spherica calf) and T6 (L. acidophillus bottle gourd + S. uberis bitter gourd + S, cerel'isiae bitter gourd). During the starter phase the gain in weight (GIW) was higher (P